Economic Burden of Cancer Attributable to Overweight in the Brazilian Unified Health System - De Moraes-Ferrari, G (ELSEVIER SCI LTD, 2022)
Background: Alongside the rising prevalence of overweight and obesity in Brazil, there is expected to be increased direct healthcare costs of cancers. Herein, we estimated the economic costs of cancer attributable to overweight in the Brazilian Unified Health System (SUS), according to sex, type of cancer and geographic location (Federative Units). Methods: The population attributable fraction (PAF) of fifteen types of cancer were estimated using body mass index (BMI) data of 85,715 adults (>= 20 years) involved in the 2019 National Health Survey and relative risks of cancers from a meta-analysis. Inpatients and outpatient procedures and costs of cancer treatment were obtained from the SUS systems. Results: Costs of cancers included in this study were Int$ 1 billion in 2019, of which 9 % or Int$ 95 million were attributable to overweight and obesity. PAFs were higher in men (11 %) than in women (8 %), while the attributable cancer costs were higher in women (Int$ 55 million) than in men (Int$ 40 million). Cancers with the highest PAFs were endometrial cancer (40 %) and esophageal cancer (26 %), whereas cancers with the highest attributable costs were colorectal cancer (Int$ 25 million) and breast cancer (Int$ 24 million). Conclusion: Overweight was responsible for approximately Int$ 95 million (9 %) cancer direct healthcare cost in Brazil. Public policies and programs aimed at encouraging healthy diets and physical activity may decrease the economic burden of cancer in Brazil.